Symposium 8: Closing the Gaps in Institutional Development of Networked Learning: How Do Policy and Strategy Inform Practice to Sustain Innovation? - Weedon, Elisabet; Jorna, Kerstin; Broumley, Liz (Proceedings of the International Conference on Networked Learning, 2004)
This paper considers the extent to which the recently developed transformation model (Martin, 2002) can usefully be applied to examine the institutional implementation of networked learning. In doing so it also examines the extent to which institutional strategy is of importance in driving such change. Four HE case studies from the JISC INLEI study provide the empirical data; however, the use of the model is exploratory at this stage as data analysis is currently ongoing. Preliminary investigation suggests that whilst some institutions go through all the earlier stages outlined by the model this is not necessarily the case for all institutions. The evidence suggests that although the four institutions included here have reached the embedded stage this may only apply to certain areas within the institution. Also considered is whether the development can be considered revolutionary or whether a continued process of evolution into a merging of traditional and IT driven delivery is more appropriate.